1982
DOI: 10.1093/infdis/146.3.388
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Pneumonitis Due to Murine Cytomegalovirus

Abstract: Virus replication and interstitial pneumonia were studied in BALB/c mice inoculated intranasally with murine cytomegalovirus (MCMV). In normal mice MCMV replicated in lung tissue but did not produce any consistent histologic abnormalities through day 21. The addition of a single dose of cyclophosphamide (0.20 mg/g) 24 hr after virus inoculation resulted in a slight increase in lung virus titers on day 10. No histologic abnormalities were noted before day 10. However, 22 or 32 virus-infected mice treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

1984
1984
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 38 publications
4
56
1
Order By: Relevance
“…infection may be influenced by differences in virus titres in the spleen. Our data are consistent with those of Shanley et al (1982), who reported similar virus titres in lung, liver and salivary gland of BALB/c mice following intranasal (i.n.) infection.…”
Section: Effect Of Route Of Inoculation On Pathological Changes In Lusupporting
confidence: 93%
See 2 more Smart Citations
“…infection may be influenced by differences in virus titres in the spleen. Our data are consistent with those of Shanley et al (1982), who reported similar virus titres in lung, liver and salivary gland of BALB/c mice following intranasal (i.n.) infection.…”
Section: Effect Of Route Of Inoculation On Pathological Changes In Lusupporting
confidence: 93%
“…His results seem to be due to the particular strain of mice he used. Unfortunately, since this strain is no longer available the reason for their exceptional sensitivity to MCMV remains a mystery (Shanley et al, 1982).…”
Section: Effect Of Route Of Inoculation On Pathological Changes In Lumentioning
confidence: 99%
See 1 more Smart Citation
“…The virus has been maintained by serial passage in BALB/c mice and prepared as a 10~ (w/v) homogenate of salivary gland tissue. For these experiments, the virus was passed once in tissue culture using mouse embryo cells (MEC) and aliquots were prepared from clarified tissue culture supernatants (Shanley et al, 1982). The inoculum for mock-infected controls was prepared by heating the virus inocutum at 56 °C for 60 min to destroy viable MCMV.…”
Section: Methodsmentioning
confidence: 99%
“…In order to gain insight into the potential mechanisms operating in CMV interstitial pneumonitis, we have been evaluating a murine model of murine CMV (MCMV) interstitial pneumonia. We previously reported that BALB/c mice inoculated with MCMV and given a single dose of cyclophosphamide (CP) develop interstitial pneumonia not seen with MCMV or CP alone (Shanley et al, 1982). These studies also suggested that immunopathogenic factors contribute to the interstitial pneumonia in this model.…”
Section: Introductionmentioning
confidence: 93%